A 50 kW PEMFC Pilot Plant Operated with Industry Grade Hydrogen – System Design and Site Integration1. Issue 5 (4th March 2014) - Keränen, T. M.; Karimäki, H.; Nikiforow, K.; Kukkonen, S.; Uusalo, H.; Viitakangas, J.; Ihonen, J.; Jones, Deborah; Jaouen, Frederic; Taillades‐Jacquin, Mélanie; Bucheli, Olivier
Abstract The chlor‐alkali industry produces high amounts of hydrogen as a by‐product of processes based on electrolytic cells. In order to improve the process' efficiency, plant operators seek ways to utilize this potential and fuel cells offer a sensible solution, producing electricity at high efficiency. PEMFC has already been demonstrated to be successful in this niche market application with a few commercial scale installations. In the DuraDemo project, a 50 kW stationary PEMFC pilot plant has been designed in a publicly funded national project involving partners from different parts of the value chain. The plant serves as an experimental platform for evaluation of BoP and power electronics components, as well as hydrogen quality studies. The system design is targeted to be commercially viable and a large amount of extra instrumentation and experimental monitoring equipment are utilized in the pilot plant to analyze its behavior. The pilot plant is fully automated and capable of independent operation with remote monitoring and data logging capability. The system design of the pilot plant is presented, including BoP component selection and characterization of the main components. Final assembly testing results, integration of the plant at its demonstration site and safety analysis work will be reported.